Nursing theorists and their work (Eighth edition) - Alligood, Martha Raile; Tomey, Ann Marriner (Elsevier, 2020)
A classic in the field of nursing theory! This renowned textbook guides the reader through in-depth descriptions and analyses of 31 specific nursing theories - many reviewed and validated by the theorists themselves - in a logical, consistent chapter organization that makes information easy to follow. Its comprehensive and thorough approach, objective critiques, and clear writing style make it ideal for the study of theory at all levels of nursing. Twelve new chapters and updated material throughout this edition provide a wealth of information on the most current and cutting-edge ideas in nursing theory today.